All inkjet‐printed 6.95″ 217 ppi active matrix QD‐LED display with RGB Cd‐free QDs in the top‐emission device structure. Issue 5 (27th April 2022) - Park, Myoungjin; Kim, Young Il; Jung, Yun Ku; Kang, Jin‐goo; Kim, Sehun; Ha, Jaekook; Yoon, Yeo‐geon; Lee, Changhee
Abstract: Electroluminescence quantum dot devices (QD‐LEDs) show the promise in the development of future displays. For commercialization, the top emission device structure is more advantageous than the bottom emission device structure to realize the high aperture ratio full color displays. Moreover, it is essential to understand not only the device structure and characteristics of QD‐LEDs but also the challenging issues in inkjet‐printed devices. Here, we demonstrated the world first all inkjet‐printed Cd‐free active matrix QD‐LEDs based on getting over the hurdles of all inkjet printing process. Especially, we have fabricated QD‐LED devices by stacking 4‐soluble layers without intermixing and studied the factors affecting QD efficiency and QD printing and the influence of ETL solvent on QD. Inkjet‐printed QD‐LED devices have achieved 8 cd/A, 70 cd/A, and 8 cd/A current efficiency of red, green, and blue, respectively, on the basis of 250 nits of full white RGB panels. We believe that our work clarifies an encouraging step toward the practical application of Cd‐free based QD‐LED displays. Abstract : We demonstrated all inkjet‐printed 6.95″ 217 ppi Cd‐free active matrix QD‐LEDs based on getting over the hurdles of all inkjet printing process. Especially, we have fabricated QD‐LED devices by stacking 4‐soluble layers without intermixing and studied the factors affecting QD efficiency and QD printing and the influence of ETL solvent on QD.